Shrimps, turtles and talks - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
The United States has recently banned the import of shrimps from Guyana and other countries because the fishing nets used to catch them could endanger marine turtles. Shrimp-producing countries filed an appeal at the World Trade Organisation, which...